Pemberdayaan Kader Kesehatan melalui Skill for Accident and Emergency sebagai Upaya Pencegahan Kecacatan dan Kematian di Desa Lawe Kihing Kecamatan Bambel Kabupaten Aceh Tenggara - Eliati Eliati; Devi Susanti; Taufik Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Health problems related to critical conditions most often occur in everyday life. Critical conditions that can occur suddenly include traffic accidents, poisoning, exposure to hot oil or hot water, and swallowing small objects. This can have an impact on disability and death. The main causes of death due to injury are traffic accidents, suicide, falls, drowning, and poisoning. Handling critical conditions must be done quickly using trained skills. Therefore, people need to get basic skills in handling critical cases. The solution to the problem in the Emergency Response Assisted Village Development program through Skills for Accident and Emergency in Increasing Community Independence as an Effort to Prevent Injury and Death in Lawe Kihing Village, Bambel District, Southeast Aceh Regency, namely forming health cadres, basic life support training, early treatment of burns, poisoning and First Aid, Establishing an Mou with the Hospital for the patient transfer process, SkACy_Ku Module, and ongoing assistance through the SkACy_Ku Module. The results of the activities achieved were that the majority of health cadres had good knowledge and skills regarding emergency case-handling actions.